Worldwide panorama of bruxism and patients with disabilities: a bibliometric analysis in PubMed (1965-2021) (Research, Society and Development, 2022)
This study aimed to present a bibliometric analysis about the central topic bruxism and disabled people in a global panorama through PubMed database (1965-2021). It was included in this study only journal publications in English. Letters to editor, short communication, articles irrelative to people with disabilities and bruxism or articles with unavailable abstract or full text were not included. The initial search was performed by three independent investigators who assessed the title, abstract and main text to determine the included or excluded articles. It was observed that the tendency of publications was rising, with an average of 1.9 per year. There were 27 countries that have contributed to publications on the studied field and the most productive ones are United States (28.2%) and Brazil (20.0%). The most productive authors in the field are Brazilian and among the most productive institutions, 4 are Brazilian and 3 are North American. Case reports were the most frequent type of article (28.1%), followed by cross-sectional studies (24.5%) and literature reviews (12.7%). The most productive journal in the studied field were Special Care in Dentistry (12.7%), followed by Journal of Oral Rehabilitation (3.6%). Brazil has a great scientific contribution to the field with a relevant number of publications, leading authors and institutions. There is a lack of high-quality evidence involving the main topic, reinforcing that further interventional studies and controlled trials must be conducted.